Hubungan Kualiti Kehidupan Kerja (QWL) Dengan Tahap Kepuasan Kerja Anggota Pangkat Rendah Konstabel Polis DiRaja Malaysia, Satu Kajian Di Jabatan Siasatan Jenayah, Ibu Pejabat Polis Daerah, Petaling Jaya, Selangor Darul Ehsan - Idris, Abdullah (2002)

(untitled)
This study examines the level of job satisfaction and relationship with the quality work of life among junior rank police officers & constables, at Criminal lnvestigation Department, District Police Headquarters, Petaling Jaya, Selangor. The objectives of this study are to investigate ; i) the relationships between quality work of life and job satisfaction among junior rank police officers & constables, at Criminal lnvestigation Department, District Police Headquarters, Petaling Jaya, Selangor. ii) The differences of the level of satisfaction among junior rank police officers & constables, at Criminal lnvestigation Department, District Police Headquarters based on demographic factors. iii) The relationships quality work of life with high job satisfaction and low job satisfaction among junior rank poiice officers & constables, at Criminal lnvestigation Department, District Police Headquarters, Petaling Jaya, Selangor. iv) The appropriateness of Walton's model as a framework for explaining job satisfaction among junior rank police officers & constables, at Criminal lnvestigation Department, District Police Headquarters, Petaling Jaya, Selangor. A set of questionnaires containing 68 items using five-points likert scale was applied to measure the assessment officers responses toward dependent and independent variables. Data has been gathered using questionnaire developed from 102 assessments among junior rank police officers & constables, at Criminal lnvestigation Department, District Police Headquarters, Petaling Jaya, Selangor. Sixteen hypotheses were constructed for this study. Statistical analysis used includes frequency, mean, median, mode, standard deviation, pearson correlation, t-test, and one-way analysis of variance (ANOVA). The result indicates ; i) significant relationships between quality work of life and job satisfaction among assessment junior rank police officers 8 constables, at Criminal lnvestigation Department, District Police Headquarters, Petaling Jaya, Selangor. ii) No significant differences in the level of satisfaction among junior rank police officers & constables, at Criminal lnvestigation Department, District Police Headquarters based on demographic factors. iii) Significant relationship between quality work of life with high job satisfaction and low job satisfaction among junior rank police officers & constables, at Criminal lnvestigation Department, District Police Headquarters, Petaling Jaya, Selangor. iv) The Walton's model is relevant and appropriate to be used as a framework for explaining job satisfaction among junior police officers & constables, at Criminal lnvestigation Department, District Police Headquarters, Petaling Jaya, Selangor.